Adoption of international financial reporting standards (IFRS) and financial performance of deposit money banks in Nigeria / Adeduro Adesola Ogunmakin, Bamikole Samson Fajuyagbe and Micah Juwon Akinleye - Ogunmakin, Adeduro Adesola; Fajuyagbe, Bamikole Samson; Akinleye, Micah Juwon (Universiti Teknologi MARA, 2021)
The study explored adoption of the International Financial Reporting Standards (IFRS) on financial performance of banks in Nigeria over a time period of ten years spreading over from 2006 to 2016. Data set utilized were randomly gathered across 10 (ten) banks, and analyzed with the use of pooled OLS, fixed effect and random effect estimations alongside the F-test and Hausman test. Result showed that embracing IFRS had insignificant positive effect on ROA of banks in Nigeria (β=0.0038609 p=0.366). It was likewise shown that loan to deposit ratio had a significant negative influence on return on asset (β=-0.0017625 p=0.046). The study established that IFRS implementation had not significantly spurred financial performance of banks in Nigeria, however it has the possibility of doing as such if banks can completely receive and fuse all parts of the Standard in their monetary detailing structure. Subsequently, it is suggested that Regulatory Authorities of deposit money banks should set up an administrative board that will be burdened with the obligation of following the pace of adoption of the IFRS in the country.